Introduced Monkey Populations of Florida - History, Status, and Potential Impacts - C. Jane Anderson; Audrey C. Wilson; Deborah "Missy" Williams; Mark E. Hostetler; Steven A. Johnson (EDIS)
At least nine populations of non-human primates have established in Florida since the 1930s. These include three species: rhesus macaques (Macaca mulatta), vervet monkeys (Chlorocebus sabaeus), and squirrel monkeys (Saimiri sp.). Invasion success has varied among the three species. As of 2021, a single, growing population of rhesus macaques was present in central Florida; a single, stable population of vervet monkeys was present in south Florida; and only two squirrel monkeys remained of a previous population on a private property in south Florida. Demonstrated and potential impacts of the three species also varied. Continued monitoring and research of introduced primate populations in Florida is critical to better understand impacts and management needs.